Kaperfart i Danmark-Noreg. Ca. 1700-1814 i lys av teoriar om statleg valdsmonopol - Kvalvik, Edvard (The University of Bergen, 2018)
The major theme for this master thesis is Danish and Norwegian privateering between the start of the 18th century until the end of the Napoleonic Wars in 1815. The main goal is to explore: To what extent did the state control privateering in the early modern states in the context of theories on state violence monopoly. The thesis starts with a depiction of the different theories on monopoly of violence and what that means for privateering. Especially the writing of Janice E Thomson, Alexander Tabarrok and Halvard Leira & Benjamin de Carvolho will be used in this master thesis. Furthermore, the subject is divided into three different aspects of Danish and Norwegian privateering: 1. The Danish-Norwegian policy on privateers and privateering, using sources on laws and regulations 2. Exploring the privateering practice using: from letter of marque and the bill of prizes. 3. Examine the size and structure of the Danish and Norwegian privateering fleet. The source material and my findings on privateering under the Northern Wars and the Napoleonic Wars are compared to the theories on state and non-state violence. This paper also compares the privateering fleet with the Danish and Norwegian national navy during two war periodes. In the 18th century, Denmark-Norway experienced a period of peace between two long wars: The Great Northern War (1700-1721) and the Napoleonic Wars (1800-1815). During this this interwar period, they acted as a neutral power in European conflicts." In both, Denmark-Norway used privateers, but banned the practice in peace time. They even tried to abolish the use of privateers in the Baltic and Nordic sea. In this thesis I look at the use of privateers in both Wars, and how the practice evolves in a hundred-year period. The thesis ultimately suggests that Denmark-Norway had little direct control in regards of what a privateer did during a raid, instead, they but compensated with strict laws before and after the raid was completed. During the Napoleonic Wars the privateering fleet was, by ...